Pengaruh Social Media Marketing Instagram Terhadap Minat Beli Konsumen di Tel-U Store - Novliana, Siska Zuherni; Cahyani, Leni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Today, technological developments are developing rapidly and have a positive impact on the field of marketing. The digital era as it is now allows products to be known and in demand through social media. Social media is a strategic marketing tool that influences consumer trust and purchase intention. The good use of social media, especially Instagram, can increase buying interest. This research uses quantitative methods with primary and secondary data obtained through interviews, questionnaires, observation, and literature study. The sample consists of 100 Instagram users who know Tel-U Store products, and the analysis is carried out using SPSS software. The results of the study show that the Instagram Tel-U Store social media marketing strategy is still effective, and customer buying interest is also high. There is a significant relationship between Instagram social media marketing and customer buying interest at Tel-U Store.